The Effect of Intellectual Capital, Corporate Social Responsibility, Good Corporate Governance, and Capital Structure on Firm Value - Nabila Az’zahra Maharani; Akhmad Riduwan; Kurnia (SOSIOEDUKASI, 2026)
This study aims to examine the effect of intellectual capital, corporate social responsibility, good corporate governance, and capital structure on firm value. In this study, intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC), corporate social responsibility is measured using the CSR index, and good corporate governance is measured through internal control mechanisms using a factor score consisting of four dimensions: the board of commissioners, the audit committee, management, and shareholders. Meanwhile, capital structure is measured using the Debt to Equity Ratio (DER), and firm value is measured using Tobin’s Q. The population of this study consists of healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. The sampling technique used in this study is purposive sampling, resulting in a total of 28 companies. To test and analyze the data, this study employs SPSS (Statistical Product and Service Solutions) version 26. The results of this study indicate that intellectual capital and capital structure have a positive effect on firm value. Meanwhile, corporate social responsibility and good corporate governance variables are found to have no significant effect on firm value.